Psychopharmaceuticals Associated with Psychotherapy (Research, Society and Development, 2022)
Objective: to describe the main aspects related to suicidal ideation in the elderly, identifying the activities developed by the psychologist. Data collection took place on the VHL (Virtual Health Library) and SCIELO (ScientificElectronic Library Online) platforms. Methodology: descriptive, exploratory, qualitative research, of the literature review type. Data collection took place on the BVS (Virtual Health Library) and SCIELO (ScientificElectronic Library Online) platforms. Results: The techniques are related to psychodynamics and the theoretical-philosophical assumptions, objectives and resources used were: interpretation, exposition, psychoeducation, frequency of sessions and duration of treatment proved to be relevant, setting (group, family, individual). In addition, therapist training is a prerequisite for an adequate therapeutic response. Conclusion: It was observed that it is important to identify risk factors related to depression. Knowledge about the multifactors helps us to reflect on the impact of socioeconomic factors, as well as the profile of the client who uses psychotropic drugs. Such information should be used in the reception process and definition of therapies.